BrMYB116 transcription factor enhances Cd stress tolerance by activating FIT3 in yeast and Chinese cabbage - Anwar, Ali; Yuan, Chao; Cui, Bing; Wang, Lixia; He, Lilong; Gao, Jianwei (Frontiers in Plant Science, 2024)
Cd (Cadmium) is a highly toxic heavy metal pollutant, often present in soil and detrimentally impacting the production and quality of horticultural crops. Cd affects various physiological and biochemical processes in plants, including chlorophyll synthesis, photosynthesis, mineral uptake and accumulation, and hormonal imbalance, leading to cell death. The MYB family of transcription factors plays a significant role in plant response to environmental influences. However, the role of MYB116 in abiotic stress tolerance remains unclear. In this study, we reported that Chinese cabbage transcription factor BrMYB116 enhanced Cd stress tolerance in yeast. The expression level of BrMYB116 was increased by Cd stress in Chinese cabbage. Additionally, yeast cells overexpressing BrMYB116 showed improved Cd stress tolerance and reduced Cd accumulation. Moreover, we found that BrMYB116 interacted with facilitator of iron transport (FIT3) to enhance Cd stress tolerance.ChIP-qPCR results showed ScFIT3 was activated through specific binding to its promoter.Additionally, the overexpression of ScFIT3 induced Cd stress tolerance and reduced Cd accumulation in yeast and Chinese cabbage. These results suggest new avenues for plant genomic modification to mitigate Cd toxicity and enhance the safety of vegetable production.